Organizational Citizenship Behaviour As Seen in The Framework-Family Conflict and Perception of Organizational Support - Rusmalia Dewi; Gusti Yuli Asih; Mulya Virgonita Iswindari Winta (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Organizational Citizenship Behavior in modern organizations has an influence on the success of the organization and the personal lives of employees. Studies related to work-family conflict and Perception of Organizational Support are some that are correlated and some that are not correlated with Organizational Citizenship Behavior, besides that there is no combination of the two. This study combines the two to find out how much influence they have on Organizational Citizenship Behavior. The purpose of this study is to empirically test the role of Work-Family Conflict and Perception of Organizational Support on Organizational Citizenship Behavior. The method used is quantitative. The subject of the study is automotive marketing. Statistical analysis with Multiple Regression Test. The sampling method uses saturated sampling. The results of this study indicate that Work-Family Conflict and Perception of Organizational Support have a significant influence on Organizational Citizenship Behavior. Perception of Organizational Support has a greater influence on Organizational Citizenship Behavior. compared to Work-Family Conflict. A small contribution to Work-Family Conflict due to the support system in Indonesian culture. In conclusion, Organizational Citizenship Behavior can be predicted from an individual's ability to manage their work-family conflict and the individual's positive perception of their organizational support.